(untitled) (Research, Society and Development, 2017)
The project here presented aims to discuss the context of emergency and development of the Production Engineering in academic environments in Brazil and South Korea. The comparison makes sense taking into account that both countries started their Science and Technology policies from similar points, back in the 1960s and 1970s decades. However, the way these trajectories differ can be understood by the way each country invested in Applied Science training, such as Industrial Engineering. Starting by the comparison of undergraduate programs from both countries, using multivariate statistics, it is possible to discuss how the Industrial Engineering is thought and developed, the main issues related to curriculum innovation and how each environment differ in terms of engineering profession.